TEACHING SPEAKING THROUGH STORYTELLING : A Case Study at a Year Ten Class of a MAN in Kendari - Asniatih ST, - (2009)
This thesis portrays the process of teaching speaking through storytelling in which students may get involved in the learning activities. This study was conducted as an effort to solve one of the problems of many EFL teachers in Indonesia, particularly in their speaking classroom where most students could not take part optimally in speaking activities. Therefore, this study is aimed at (1) describing how speaking is taught through storytelling; and (2) elaborating the kinds of oral production that the students carried out during the process. The result of the present study is expected to contribute to the teaching and learning field and further research. In conducting the study, a qualitative case study is employed to better understand the phenomena. Two techniques were used to collect the data, classroom observation which was conducted for five meetings and questionnaire which was administered to the students after the five observations. During the observation, MP3 and digital camera were used to record the situations and interaction as well as the activities performed by the teacher and students. Field notes were also taken to complete the data collected. The research context for this study is a MAN in Kendari. This involves a teacher and 31 students in a year ten class. As this teaching program was never performed yet in the research context and that the researcher is one of the staff in the school, participant observation was conducted in which the researcher acted as the teacher. The data collection and analysis were done simultaneously during this study. The results from both data collection were directly compared and interpreted. Analysis of observation and questionnaire data shows that there were some ways that the teacher used when teaching speaking through storytelling. The ways included some activities she did before, during, and after her storytelling. The results of this study also show that teaching speaking through storytelling was conducted integrated with other skills, such as listening, reading, and writing skills. The use of storytelling in the teaching of speaking enabled students not only to engage in the learning but also to get a meaningful learning experience. The analysis also shows that the kinds of oral production that the students carried out extensive (monologue), transactional (dialogue), responsive, and imitative oral production during the learning. Nevertheless, it was only dominated by extensive (monologue). It was due to the nature of storytelling activities and the students' limited English. With reference to the findings, it is recommended that it would be important if the storytelling technique is trained to other EFL teachers in order to be implemented in their teaching practice. Also, further research on using storytelling in the teaching program is still open widely for developing other language skills, such as listening, reading, and writing as well as developing the students' vocabulary, appreciation on literature, and critical thinking.